PENEGAKAN HUKUM TINDAK PIDANA KORUPSI DI INDONESIA TERHADAP PELAKU KORPORASI (Jurnal Magister Hukum Perspektif, 2019)
Law enforcement in Indonesia in the case of Corruption Crimes outlined in Transparency International (IT) data Indonesia is still considered the most corrupt. Such conditions require the handling of criminal acts that are "extraordinary" (extra-ordinary enforcement) including law enforcement against corporate actors. Currently, the enforcement of tipikor law against corporate actors is not only focused on the person / manager but also focused on the corporation. In the Tipikor Law, the law enforcement of corporate actors uses 3 doctrines namely identification theory, vicarious liablity and strict liability and the model of criminal liability using administrators can be accounted for criminal together with corporations. Related to the procedures of law enforcement tipikor conducted by the corporation based on the knowledge and experience of each law enforcement officer and to overcome the problem MA issued Perma Number 13 of 2016 on Procedures for Handling Criminal Acts by Corporations. This is done to fill the legal void related to the handling of criminal acts with corporate actors who have not been clearly and firmly regulated. Enforcement of tipikor law by corporations experiencing several obstacles, among others, the main criminal sanctions are only in the form of fines {article 20 paragraph (7) of the Tipikor Law, which if the perpetrator does not want to pay there is no other alternative. The death penalty in article 2 paragraph (2) of the Tipikor Law cannot be applied to corporations. In addition, Perma Number 13 of 2016 cannot be used as a reference by investigators or public prosecutors because the Perma is binding into including criminal sanctions are still in the form of fines, have not regulated the mechanism of withdrawal of corporate criminal liability. Keywords : Law Enforcement, Criminal Acts, Corruption, Corporations